2017
DOI: 10.1101/220293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phospho-signal flow from a pole-localized microdomain spatially patterns transcription factor activity

Abstract: Selective recruitment and concentration of signaling proteins within membrane-less compartments is a ubiquitous mechanism for subcellular organization. However, little is known about the effects of such a dynamic recruitment mechanism on intracellular signaling. Here, we combined transcriptional profiling, reaction-diffusion modeling, and single-molecule tracking to study signal exchange in and out of a microdomain at the cell pole of the asymmetrically dividing bacterium Caulobacter crescentus. Our study reve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 125 publications
(246 reference statements)
1
13
0
Order By: Relevance
“…Additionally, oligomerization of CckA is critical for DivL stimulation of kinase activity but not its stimulation of CckA phosphatase activity. While we must keep in mind that this reconstitution approach represents a simplified system that lacks additional factors present in vivo , our previous experiments using reconstituted CckA on liposomes have been supported by subsequent work demonstrating agreement that the CckA surface density that is critical for kinase activity in our in vitro experiments matches the surface density of CckA present at the new cell pole in vivo (22). In this study, we reconstitute an additional aspect of subcellular regulation of CckA.…”
Section: Introductionsupporting
confidence: 64%
“…Additionally, oligomerization of CckA is critical for DivL stimulation of kinase activity but not its stimulation of CckA phosphatase activity. While we must keep in mind that this reconstitution approach represents a simplified system that lacks additional factors present in vivo , our previous experiments using reconstituted CckA on liposomes have been supported by subsequent work demonstrating agreement that the CckA surface density that is critical for kinase activity in our in vitro experiments matches the surface density of CckA present at the new cell pole in vivo (22). In this study, we reconstitute an additional aspect of subcellular regulation of CckA.…”
Section: Introductionsupporting
confidence: 64%
“…While BR-bodies and CcmM-Rubisco condensates are currently the only bacterial biomolecular condensates whose components have been directly shown to form liquid-like droplets in physiological conditions (Al-Husini et al, 2018; Wang et al, 2019), the cell division protein FtsZ and its inhibitor SlmA were shown to form condensates upon addition of crowding reagents (Monterroso et al, 2019). In addition, other bacterial proteins such as the polar protein scaffold PopZ (Lasker et al, 2018; Zhao et al, 2018) and the nucleoid associated protein DPS (Janissen et al, 2018) have been shown to act as selectively permeable scaffolds, yet biomolecular condensation has not been directly observed.…”
Section: Discussionmentioning
confidence: 99%
“…Tracking CysRsaA anchored to the LPS outer membrane while utilizing a double helix point-spread function for 3D localization 18 allowed calculation of an apparent diffusion coefficient, D=0.077 µm 2 /s (Figure 4e, Methods). A comparison with the recent SMT of a similarly sized transmembrane signaling protein anchored to the inner membrane of C. crescentus , CckA (D=0.0082 µm 2 /s) 32 , reveals that CysRsaA diffuses an order of magnitude faster.…”
Section: Main Textmentioning
confidence: 93%